ANALYSIS OF SOME MEDICINAL SPECIES OF THE GENUS ACHILLEA L (Scientific journal of the Fergana State University, 2025)
The main species belonging to the genus Achillea grow in various ecological environments and are distinguished by their therapeutic properties. This analytical article provides an extensive overview of the morphological characteristics, phytochemical composition, and medicinal applications of species such as A. filipendulina, A. millefolium, A. grandifolia, and A. wilhelmsii. These plants contain biologically active compounds, including essential oils, flavonoids, sesquiterpenes, and monoterpenes. These biologically active substances have been isolated from different parts of the plants in various studies and used in medicine for the treatment of diseases. A. filipendulina is notable for its anti-inflammatory and antiseptic properties, while A. millefolium is effective in treating gastrointestinal diseases. Today, this plant is also widely used in the cosmetics industry as a skin-whitening, moisturizing, and cleansing agent. A. grandifolia is mainly employed in the treatment of gastrointestinal disorders. A. wilhelmsii is widely used in traditional medicine to treat abdominal pain, diabetes, and obesity. Further in-depth studies of the chemical composition of the Achillea genus and the confirmation of their medicinal properties through clinical research are essential.